2014
DOI: 10.1002/ana.24284
|View full text |Cite
|
Sign up to set email alerts
|

A new muscle glycogen storage disease associated with glycogenin‐1 deficiency

Abstract: We describe a slowly progressive myopathy in 7 unrelated adult patients with storage of polyglucosan in muscle fibers. Genetic investigation revealed homozygous or compound heterozygous deleterious variants in the glycogenin-1 gene (GYG1). Most patients showed depletion of glycogenin-1 in skeletal muscle, whereas 1 showed presence of glycogenin-1 lacking the C-terminal that normally binds glycogen synthase. Our results indicate that either depletion of glycogenin-1 or impaired interaction with glycogen synthas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
88
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 81 publications
(102 citation statements)
references
References 14 publications
12
88
2
Order By: Relevance
“…The patient was found to have free but autoglucosylated glycogenin-1 in muscle, similar to what is seen in glycogen synthase deficiency (Malfatti et al, 2014). The impaired elongation of the glucose polymer by glycogen synthase can be explained by the fact that glycogen synthase normally binds to the C-terminus of glycogenin-1 (Skurat et al, 2006), and that this binding may be of functional importance.…”
Section: Molecular Geneticssupporting
confidence: 61%
See 3 more Smart Citations
“…The patient was found to have free but autoglucosylated glycogenin-1 in muscle, similar to what is seen in glycogen synthase deficiency (Malfatti et al, 2014). The impaired elongation of the glucose polymer by glycogen synthase can be explained by the fact that glycogen synthase normally binds to the C-terminus of glycogenin-1 (Skurat et al, 2006), and that this binding may be of functional importance.…”
Section: Molecular Geneticssupporting
confidence: 61%
“…The missense variant p.Asp102His, described in one patient (Malfatti et al, 2014), has also been identified in other patients (unpublished data). According to the EVS server, this mutation has been found in 17/13 006 alleles.…”
Section: Molecular Geneticsmentioning
confidence: 70%
See 2 more Smart Citations
“…Compound heterozygous mutations in the glycogenin-1 gene (GYG1) were first found to cause cardiomyopathy with arrhythmia in a patient with glycogen depletion in muscle and PAS-positive inclusions in cardiomyocytes [4]. Later, seven additional patients with glycogenin-1 deficiency were found with manifestation as lateonset muscle weakness with polyglucosan deposits confined to skeletal muscle [5].…”
Section: Introductionmentioning
confidence: 99%